2017
DOI: 10.1172/jci93924
|View full text |Cite
|
Sign up to set email alerts
|

Cografting astrocytes improves cell therapeutic outcomes in a Parkinson’s disease model

Abstract: In this study, we have attempted to exploit the neurotrophic actions of astrocytes and Nurr1+Foxa2 functions in this cell type to improve the therapeutic outcomes of NPC transplantation using an animal model of PD. Our in vitro assays using a coculture system and conditioned media treatment revealed that astrocytes, especially those cultured from the ventral midbrain (VM), where HNF3β) is a potent cofactor that synergizes the Nurr1-mediated antiinflammatory roles in glia (16). Furthermore, forced coexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 83 publications
2
65
0
3
Order By: Relevance
“…Based on this background, VM-As appear uniquely positioned to drive neuroprotective and regenerative programs in PD, and recent preclinical studies used co-transplantation of As to promote the regenerative effects of co-transplanted stem cells in rodent PD models (Yang et al, 2014;Song et al, 2018). However, how the aged brain responds to pharmacological or cellular therapeutical interventions is not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this background, VM-As appear uniquely positioned to drive neuroprotective and regenerative programs in PD, and recent preclinical studies used co-transplantation of As to promote the regenerative effects of co-transplanted stem cells in rodent PD models (Yang et al, 2014;Song et al, 2018). However, how the aged brain responds to pharmacological or cellular therapeutical interventions is not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study found that most implanted cells were localized in the transplant area, and only a few of them were observed in the striatum of PD rats in the NNSC + NMG group after months (Figure ). Based on the results and previous studies, the molecular mechanisms underlying the neuroprotective effects of Nurr1 on PD included the reduction of inflammatory factors and the secretion of neurotrophic factors and other cytokines, such as SHH and FGF8 …”
Section: Discussionmentioning
confidence: 98%
“…Importantly, the key obstacles to the success of preclinical trials in PD are the poor survival of grafted cells . After cell transplantation, the hostile host brain environment is mainly responsible for unsatisfactory results . A few studies targeted the host brain to improve therapeutic effects .…”
Section: Discussionmentioning
confidence: 99%
“…B. kontinuierlich neurotrophe Faktoren zu sezernieren, wie erfolgreich in Tiermodellen gezeigt werden konnte [20,105]. Der neurorestaurative Effekt nach Transplantation von neuronalen Vorläuferzellen in das Striatum wird durch begleitende Transplantation von Astrozyten deutlich verbessert [106]. Noch eleganter ist ein Ansatz, der eine Zelltransplantation vermeidet und Astrozyten direkt im Striatum in situ mittels stereotaktisch applizierter lentiviraler Gen-Vektoren zu dopaminergen Zellen umwandelt, damit sie die Funktion der degenerierten dopaminergen Neurone übernehmen [107].…”
Section: Therapeutische Optionen Und Potential Der Immunmodulationunclassified